UJI KANDUNGAN LOGAM BERAT TIMBAL (Pb) PADA KANGKUNG AIR (Ipomea aqutica F) DI KAMPUS UNPATTI POKA - Daviesten Katipana (BIOPENDIX, 2015)
Background: Kale is a vegetable that is widely consumed by the public and this vegetable is a good source of vitamin A which is very good. Complex regional Pattimura University in Ambon many people grow vegetables, among which are vegetable kale. Many around the farm population in fear that this vegetable has been exposed to metallic lead (Pb) the purpose of this study is to determine the metal content of lead (Pb). Methods: Sampling of water spinach (Ipomea aquatica F) done at two stations that have been determined, which covers parts of stems, young leaves and old leaves. Parameters taken from the water sample as the growth of plant water spinach (Ipomea aquatica F.) is a heavy metal content using Vogel quantitative method. Results: Determination of the content of Pb were analyzed using Atomic Absorption Spectrophotometer (AAS). The results showed the average content at the first station for young leaves, 0.283 ppm, old leaves, 0.200 ppm, rods, 0.283 ppm, and the water is not detected and station II respectively of young leaves, 0.283 ppm, young leaves, 0.200 ppm, rod, 0.533 and water are not detected while the residue Pb safe limits allowed by the Directorate General of POM on food only 2 ppm so the heavy metals in water spinach is still feasible for consumption. Conclusion: Based on the results of research conducted, it can be concluded that the heavy metal content in the organs of the stem, the leaves of old and young leaves of kale Water plant (Ipomea aquatica F.) at stations I and II stations are significant differences which include the trunk station I , II (0, 283, 0.533 ppm), older leaves station I, II (0, 0.200, 0.283 ppm), young leaves station I, II (0, 283, 0.200 ppm) and water at station I, II undetected.